Knowledge of the Nutrition of Pregnant Women on the Incidence of Chronic Energy Deficiency - Gumanti, Kentri Anggarina (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2023)
Pregnant women with Chronic Energy Deficiency (CED) are pregnant women who are at risk of experiencing Chronic Energy Deficiency, which is characterized by an upper arm circumference (LILA) below 23.5 cm. Most pregnant women in rural and urban areas experience a lack of energy and protein consumption so they lack macronutrients and micronutrients which can result in low birth weight babies and short toddlers. The purpose of this study was to determine the relationship between the nutritional knowledge of pregnant women and the incidence of chronic energy deficiency in pregnant women. This research method is Analytical Cross-Sectional and the sample is taken by total sampling technique, the sample size is 65 respondents. Analysis of research data using Pearson's Chi-Square Test with (α = 0.05). The results showed that p-value = 0.7259 so there was no relationship between knowledge of pregnant women's nutrition and the incidence of chronic energy deficiency in pregnant women